Peripheral Quantitative Computed Tomography Derived Muscle Density Is Associated With Physical Performance in Older Adults. (November 2021) - Martini, Sebastian; Petermeise, Sophie; Henkel, Michaela; Weiß, Stefanie; Schaupp, Anna; Ferrari, Uta; Schmidmaier, Ralf; Drey, Michael
Highlights: Peripheral quantitative computed tomography can be utilized to measure body composition in geriatric patients. Muscle density and muscle area are associated with hand grip strength even after adjusting for potential confounders. Body mass index is not the sole responsible factor for muscle fat infiltration. Abstract: Purpose: The assessment of body composition is an integral part in diagnosing sarcopenia. The purpose of this study was to determine the relationships between peripheral quantitative computed tomography (pQCT)-derived measures of body composition and measures of physical performance in older adults. Methods: Muscle density, muscle area, and fat area of 168 patients aged 65 years and older (76.3±6.5) were measured with pQCT at the distal forearm additionally to clinical assessment consisting of medical history, physical examination and physical assessment including hand grip strength, gait speed and chair rise tests. Regression analyses assessed associations between patients' physical performance and pQCT derived data. Results: Among the three pQCT parameters, especially muscle density was significantly correlated with all of the three measures of physical performance even after adjusting for sex, age, BMI, vitamin D serum level and the level of physical activity. The same analysis for muscle area achieved significance level only for handgrip strength but not for gait speed nor for chair rise time. Fat area was significantly correlated only with gait speed after adjusting for sex and age. The association of muscle density with physical performance held up in an additional subanalysis stratified by body mass index. Conclusion: Muscle density, a proxy for muscle fat infiltration, seems to be better than muscle area or fat area at assessing muscle quality and physical performance in older adults. This association seems to be independent of the body mass index.